Injection of a fluorescent microsensor into a specific cell by laser manipulation and heating with multiple wavelengths of light - Maruyama, Hisataka; Hashim, Hairulazwan; Yanagawa, Ryota; Arai, Fumihito (2021)
In this study, we propose the manipulation and cell injection of a fluorescent microsensor using multiple wavelengths of light. The fluorescent microsensor is made of a 1-μm polystyrene particle containing infrared (IR: 808 nm) absorbing dye and Rhodamine B. The polystyrene particle can be manipulated in water using a 1064-nm laser because the refractive index of the polystyrene is 1.6 (refractive index of water: 1.3). The IR absorbing dye absorbs 808-nm light but does not absorb the 1064-nm laser. Rhodamine B is a temperature-sensitive fluorescent dye (excitation wavelength: 488 nm, emission wavelength: 560 nm). The functions of manipulation, heating for injection, and temperature measurement are achieved by different wavelengths of 1064 nm, 808 nm, and 488 nm, respectively. The temperature increase of fluorescent microsensor with 808-nm (40 mW, 10 s) laser was approximately 15°C, and enough for injection of fluorescent microsensor. We demonstrated manipulation and injection of the microsensor into Madin-Darby canine kidney cell using 1064-nm and 808-nm lasers. These results confirmed the effectiveness of our proposed cell injection of a fluorescent microsensor using multiple wavelengths of light.